Women's survey instrument: Measuring impacts of training interventions on voice and agency in MGNREGA asset selection in Odisha, India - Kosec, Katrina; Kyle, Jordan; Narayanan, Sudha; Raghunathan, Kalyani; Ray, Soumyajit (International Food Policy Research Institute, 2024)
Women’s voice and agency within community decision-making is linked intrinsically with gender equality as well as with community development outcomes and women’s livelihoods. These survey modules have been piloted in Odisha, India for measuring the impacts of a training intervention to amplify women’s voice and agency, and we include translations in Odia. They can be used to measure various aspects of women’s empowerment within MGNREGA as well as adapted to measure women’s voice and agency in community decision-making more broadly. We have developed and piloted modules on: • women’s employment in MGNREGA (module A); • ownership of MGNREGA assets (module B); • women’s participation in asset selection and asset aspirations (module C); • perceptions of MGNREGA training program (module D); • membership in collective organizations and comfort with public speaking (module E); • self-efficacy (module F); and • gender norms (module G)